Adaptive plasticity of morphological and anatomical traits of Brant’s oak (Quercus brantii Lindl.) leaves under different climates and elevation gradients - Forough Soheili; Mehdi Heydari; Stephen Woodward; Hazandy Abdul-Hamid; Hamid Reza Naji (Forest Science and Technology, 2023)
AbstractThe morphological and anatomical characteristics of leaves are sensitive and adaptable to environmental changes. Determining eco-physiological patterns of leaf characteristics along elevational gradients allows for a better understanding and prediction of how plants might respond to climate change. In this work, the ecological adaptation mechanisms related to morphological and anatomical characteristics of Brant’s oak (Quercus brantii Lindl.) leaves were studied at three elevation classes (low, middle, and high) in two different Mediterranean and subhumid climates in Zagros forests in western Iran. There were no significant changes in leaf length, although the leaf-specific area was higher at low and middle elevations in subhumid climates. In addition, stomata length, width, density, and stomatal pore index were higher in the upper elevations of subhumid climate than in the Mediterranean climate. At low and middle elevations, dry matter content was higher at sites from the Mediterranean climate. The results of plasticity indices showed that individuals of Q. brantii from middle-elevation sites exhibited greater plasticity than those from low and high-elevation sites. Overall, Q. brantii, the dominant oak species in Zagros forests, appears to respond to elevational and environmental changes, suggesting that leaves can adapt to these changes through morphological and anatomical traits. These results provide new insights into the environmental adaptation strategies of plants at the morphological and anatomical levels against climate change.